Предмет: Алгебра,
автор: 45ghhh
решите тригонометрическое уравнение
Приложения:
Ответы
Автор ответа:
0
sinx-√3cosx=
sinx-√3cosx=
sinx-√3cosx=
sinx-√3cosx=
sinx-√3cosx=2
1/2*sinx-√3/2*cosx=1
1/2=sin(pi/6)
√3/2=cos(pi/6)
sinx*sin(pi/6)-cosx*cos(pi/6)=1
cosx*cos(pi/6)-sinx*sin(pi/6)=-1
cos(x+pi/6)=-1
x+pi/6=pi+2pi*n n∈Z
x=5pi/6+2pi*n n∈Z
sinx-√3cosx=
sinx-√3cosx=
sinx-√3cosx=
sinx-√3cosx=2
1/2*sinx-√3/2*cosx=1
1/2=sin(pi/6)
√3/2=cos(pi/6)
sinx*sin(pi/6)-cosx*cos(pi/6)=1
cosx*cos(pi/6)-sinx*sin(pi/6)=-1
cos(x+pi/6)=-1
x+pi/6=pi+2pi*n n∈Z
x=5pi/6+2pi*n n∈Z
Автор ответа:
0
метод ввода дополнительного аргумента
Похожие вопросы
Предмет: Биология,
автор: nzar36
Предмет: Физика,
автор: rolpal01052006
Предмет: Русский язык,
автор: sashlord5
Предмет: Обществознание,
автор: k1s8unnyagaya
Предмет: История,
автор: милоличка